Asthenozoospermia in a patient with reciprocal translocation t(12;15): A case report - Tea Mladenić; Anita Barišić; Ivan Vukelić; Antun Gršković; Nada Starčević Čizmarević; Jadranka Vraneković (Urology Case Reports, 2025)
Reciprocal translocation is a chromosomal aberration where fragments are exchanged between two non-homologous chromosomes. Its prevalence is estimated at 0.16–0.2 % in the general population, rising to 1.3 % among infertile men. We report a 34-year-old Caucasian male with asthenozoospermia who was admitted for genetic testing. G-banding revealed a reciprocal translocation between chromosomes 12 and 15, with a karyotype of 46,XY,t(12;15)(p13.2?q15). Fluorescence in situ hybridisation confirmed this translocation using specific probes for chromosomes 12 and 15. This case highlights a rare chromosomal translocation t (12; 15) (p13.2? q15) associated with asthenozoospermia. Further sequencing analysis is needed to determine the precise breakpoints and assess potential genotype-phenotype correlations.